2000
DOI: 10.1093/ajcn/72.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa inhibits platelet activation and function

Abstract: Cocoa consumption suppressed ADP- or epinephrine-stimulated platelet activation and platelet microparticle formation. Cocoa consumption had an aspirin-like effect on primary hemostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
178
1
9

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(199 citation statements)
references
References 44 publications
11
178
1
9
Order By: Relevance
“…This result is consistent with a potentially beneficial effect of black tea on platelet activation, rather than effects on endothelial cells. Our results are also supported by studies showing that polyphenols and a polyphenol-rich cocoa beverage suppress ex vivo stimulated and unstimulated markers of platelet activation (Rein et al, 2000a) and stimulated P-selectin expression (Rein et al, 2000b) in humans.…”
Section: Cell Adhesion Moleculesupporting
confidence: 85%
“…This result is consistent with a potentially beneficial effect of black tea on platelet activation, rather than effects on endothelial cells. Our results are also supported by studies showing that polyphenols and a polyphenol-rich cocoa beverage suppress ex vivo stimulated and unstimulated markers of platelet activation (Rein et al, 2000a) and stimulated P-selectin expression (Rein et al, 2000b) in humans.…”
Section: Cell Adhesion Moleculesupporting
confidence: 85%
“…35 Nevertheless, several recent reports have suggested that increased dietary flavonoid consumption may inhibit platelet activation and function in humans. 36,37 Rein and colleagues 36 randomized 30 healthy volunteers to either cocoa, a caffeine-containing control beverage, or water and found that cocoa consumption suppressed ADP-and epinephrine-stimulated platelet activation acutely and had an aspirinlike effect on primary hemostasis as measured with a platelet function analyzer. Cocoa is high in flavonoids, especially catechins, 38 and has been shown by Rein and colleagues to decrease plasma markers of oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…The first study 36 assessed markers of platelet activation and function, and the second study 37 measured whole-blood aggregation. In the present study, we assessed ex vivo platelet aggregation in plateletrich plasma, a method that has been shown to relate to CAD mortality 40 and previous myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The drink was prepared just before administration and ingested at room temperature, without applying any thermal treatment. Each drink contained 12 g of cocoa powder and 28 g of sugar according to other authors (6). MDA was prepared with 7 g of flavonoid-enriched powder plus 5 g of conventional cocoa powder while MDB was prepared with 12 g of conventional cocoa powder.…”
Section: Methodsmentioning
confidence: 99%